COMPARISON OF INTER-MAXILLARY FIXATION SCREWS WITH ARCH BARS FOR THEIR EFFECTIVENESS IN ESTABLISHING OCCLUSION BEFORE OPEN REDUCTION AND INTERNAL FIXATION IN MANDIBULAR FRACTURES - Mairaj, Wajid; Shah, Irfan; Khan, Muhammad Nazeer; Khan, Ali Akhtar; Babar, Adnan; Mahmood, Saad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the effectiveness of inter-maxillary screws in establishing occlusion over arch bars and to determine possible complications associated with both techniques.Study Design: Comparative prospective study.Place and Duration of Study: Department of Oral & Maxillofacial Surgery, Armed Forces Institute of Dentistry,Rawalpindi from Jul 2018 to Jul 2019.Methodology: Forty-four patients having mandibular fractures were selected. Participants were divided intogroup A (arch bar) and group B (inter-maxillary screws). Randomization was done through lottery method.Patients with permanent dentition and unilateral fractures in dentate area of the mandible were included inthe study. Glove punctures, time taken for establishing intermaxillary fixation, stability of occlusion, hardwaretolerability, oral hygiene and associated complications were recorded at per-op and 04 weeks follow up.Results: Glove puncture was more frequent in arch bar group 13(65%) than intermaxillary screw group 3 (13%)[p.001]. The time needed for establishing intermaxillary fixation with intermaxillary screws was less than thatof arch bar group (p